Qualite De Vie Et Vcu De La Maladie, Avant Et Apres Hystrectomie Vaginale, Chez Les Femmes Admises Au Centre Hospitalier Universitaire De Brazzaville (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: experience of the disease; vaginal hysterectomy; brazzaville congo